Electrical properties of singleand multi-walled carbon nanotubes composites at low temperatures - Karbovnyk, Ivan; Lukashevych, Dmytro; Chalyy, Dmytro; Klym, Halyna (Видавництво Львівської політехніки, 2017)
Electrical properties of single- and multi-walled carbon nanotubes composites (PEDOT:PSS/CNTs) were investigated in the range of 50 to 200 K. It is established that composite films with multi-walled nanotubes loading show lower resistances as compared to their single-walled counterpart.
Keywords: nanotube; electrical properties; low temperature; composite; polymer